The indigenous languages of ancient Sicily - Prag, JR (Institución Fernando el Católico, 2020)
This paper provides a brief synthesis of the evidence and principal points of discussion concerning the indigenous languages of ancient Sicily. Traditionally, three indigenous languages (Sikel, Sikan, and Elymian) are identified in use in Sicily in the period between the seventh and fourth centuries BCE. The evidence is extremely fragmentary, and its study is additionally complicated by the absence of up-to-date systematic collection of the material. The evidence is listed and the key points of linguistic and graphic discussion are presented. The traditional separation of Sikel and Sikan had already been challenged in existing scholarship; this paper suggests, in line with recent work, that the existing assumptions about the separation of Elymian also deserve to be challenged, and that the traditional assumptions about material and/or ethnic cultural boundaries on the island are potentially misleading. Este trabajo es una breve síntesis de los datos ciertos y principales puntos de discusión sobre las lenguas indígenas de la antigua Sicilia. Tradicionalmente, se identifican tres lenguas indígenas (sículo, sicano y élimo) en Sicilia en el período comprendido entre los siglos VII y IV a. C. Sus testimonios son muy fragmentarios. Su estudio se complica, además, por la ausencia de una recopilación sistemática y actualizada de ese material. Aquí se recaban esos testimonios y se presentan los puntos clave de discusión en los planos lingüístico y gráfico. La distinción tradicional entre sículo y sicano ya había sido cuestionada en estudios anteriores; en este trabajo se sugiere, en consonancia con las tendencias actuales, que debe cuestionarse la existencia independiente del élimo y que los supuestos tradicionales sobre los límites culturales materiales y/o étnicos en la isla son potencialmente engañosos.